Examining the Effects of Professional Competence and Professional Commitment on Lecturer Performance through Organizational Commitment - Rahindra Bayu Kumara; Zhao Jing; Ganjar Ndaru Ikhtiagung; Lodis Ramadhan; Costantein Imanuel Sarapil (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the effects of professional competence and professional commitment on lecturer performance, with organizational commitment serving as a mediating variable in maritime higher education institutions in Semarang City, Indonesia. A quantitative explanatory approach was employed using a census of 116 lecturers from three maritime higher education institutions. Data were collected through a 7-point Likert scale questionnaire and analyzed using multiple regression, path analysis, and the Sobel test. The findings indicate that professional competence and professional commitment have positive and significant effects on both organizational commitment and lecturer performance. Organizational commitment was identified as the strongest predictor of lecturer performance (β = 0.493; p < 0.001). Furthermore, organizational commitment significantly mediates the relationships between professional competence and lecturer performance, as well as between professional commitment and lecturer performance. The results suggest that lecturer performance improvement cannot rely solely on enhancing professional competence and professionalism but also requires strengthening organizational commitment. This study contributes to the human resource management literature in vocational maritime education by providing empirical evidence that organizational commitment functions as an important mechanism linking professional attributes to lecturer performance. The findings offer practical implications for maritime higher education institutions in designing integrated strategies for lecturer development and organizational strengthening.